2017
DOI: 10.1016/j.fuel.2016.10.096
|View full text |Cite
|
Sign up to set email alerts
|

Flame–wall interactions of lean premixed flames under elevated, rising pressure conditions

Abstract: Direct numerical simulation (DNS) of laminar lean methane-air and nheptane-air premixed flames with high exhaust gas recirculation (EGR) ratios propagating towards inert walls in a head-on quenching configuration is conducted to investigate flame-wall interactions at relatively high initial pressure conditions. This study considers the flame propagation under isochoric process after ignition while the piston is at top dead center (TDC). The effects of EGR ratio, equivalence ratio, initial pressure and wall tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Sotton et al (Sotton et al, 2005) investigated the effect of interaction between methane-air laminar flame and wall on quenching distance and wall heat flux in the pressure range of 0.05-1.7 MPa under dry wall condition, in which study the relationship between the maximum heat flux peak and the flame quenching distance was examined. Yenerdag et al (Yenerdag et al, 2017) found that the flame quenching distance was directly related to the wall temperature, where the peak heat flow density at the wall was the key factor affecting the quenching distance, through the utilization of a direct numerical simulation (DNS) method. Kim et al (Kim et al, 2006) investigated the quenching process of a flame inside a flat plate in a two-dimensional slit burner and found that the wall temperature had a direct effect on the heat transfer losses of the flame-wall interaction process as well as the annihilation of wall radical chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Sotton et al (Sotton et al, 2005) investigated the effect of interaction between methane-air laminar flame and wall on quenching distance and wall heat flux in the pressure range of 0.05-1.7 MPa under dry wall condition, in which study the relationship between the maximum heat flux peak and the flame quenching distance was examined. Yenerdag et al (Yenerdag et al, 2017) found that the flame quenching distance was directly related to the wall temperature, where the peak heat flow density at the wall was the key factor affecting the quenching distance, through the utilization of a direct numerical simulation (DNS) method. Kim et al (Kim et al, 2006) investigated the quenching process of a flame inside a flat plate in a two-dimensional slit burner and found that the wall temperature had a direct effect on the heat transfer losses of the flame-wall interaction process as well as the annihilation of wall radical chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Direct Numerical Simulation (Yenerdag et al, 2017), (Kondo et al, 2017) (Fuyuto et al, 2006) ( , 2011) μPIV 50μm~100m (Jainski et al, 2012), ( , 2016), 1 1 (Fujimoto et al, 2011) kHz (…”
mentioning
confidence: 99%